Nontrivial Solutions for a Class of p-Kirchhoff Dirichlet Problem - Xian Hu; Yong-Yi Lan (Discrete Dynamics in Nature and Society)
This paper is devoted to the following p-Kirchhoff type of problems −a+b∫Ω∇updxΔpu=fx,u,x∈Ωu=0,x∈∂Ω with the Dirichlet boundary value. We show that the p-Kirchhoff type of problems has at least a nontrivial weak solution. The main tools are variational method, critical point theory, and mountain-pass theorem.